1995
DOI: 10.1002/hep.1840210214
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body and segmental bioelectrical parameters in chronic liver disease: Effect of gender and disease stages

Abstract: The aim of this study was to examine and compare whole-body and segmental impedance measurements in control subjects and patients with progression of liver disease and to investigate whole-body and segmental bioelectrical changes occurring during dehydration therapy or paracentesis. Males have lower resistance (R) and reactance (Xc) values than females in measurements both of the whole body and of the arm, leg, and trunk. This is not true in patients. In the three groups of patients, whole-body R and Xc were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…P ATIENTS WITH CIRRHOSIS often have an abnormal body composition with clinical signs of protein-energy malnutrition and a relative increase in body weight due to ascites or edema. [1][2][3] Ascites is a condition that is becoming treatable with diuretics, albumin preparations, ascetic reperfusion, and transjugular intrahepatic portosystemic shunting, but the prognosis of patients with ascites remains poor. 4,5 Heuman et al studied 507 cirrhotic patients referred for consideration of liver transplantation and concluded that the presence of persistent ascites is an important independent predictor of high mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“…P ATIENTS WITH CIRRHOSIS often have an abnormal body composition with clinical signs of protein-energy malnutrition and a relative increase in body weight due to ascites or edema. [1][2][3] Ascites is a condition that is becoming treatable with diuretics, albumin preparations, ascetic reperfusion, and transjugular intrahepatic portosystemic shunting, but the prognosis of patients with ascites remains poor. 4,5 Heuman et al studied 507 cirrhotic patients referred for consideration of liver transplantation and concluded that the presence of persistent ascites is an important independent predictor of high mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“…BIVA thus measures whole-body fluid volume [47,48], has a correlation coefficient of 0.996, and a measurement error that ranges from 2 to 4%. BIVA provides data on volume status and has been validated in kidney [49], liver, and heart disease [50][51][52]. In one study using BIVA as a proxy for the adequacy of ultrafiltration in over 3,000 hemodialysis patients, BIVA indices reflecting greater soft tissue hydration (less adequate ultrafiltration) were associated with a significant increase in mortality [53].…”
Section: Bioimpedance Vector Analysismentioning
confidence: 98%
“…BIVA has been used in the analysis of volume depletion [15] as well as several volumeoverloaded disease processes, e.g. heart failure [16], kidney failure [17], and liver disease [18]. It is superior in assessing for volume overload compared to anthropometric measurements, with a sensitivity of 88% and specificity of 87% for detecting edema by vector analysis on the RXc graph [19].…”
Section: Bioimpedance Vector Analysis As An Indicator Of Volume Statusmentioning
confidence: 99%